Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Pada Materi Elektrokimia - Isranti Nurul Choiriyah; Masriani Masriani; Rahmat Rasmawan; Erlina Erlina; Rody Putra Sartika (Hydrogen: Jurnal Kependidikan Kimia, 2022)
The aim of this study was to see how learning results differ before and after using the Problem Based Learning (PBL) model, as well as to see how the PBL learning model affects the electrochemistry material in class XII IPA SMA N 11 Pontianak. The form of research used with a research sample of 35 persons was pre-experimental using a one-group pretest-posttest design. Pre-test and post-test data collecting methods were used. The normality test with the Shapiro-Wilk test was employed in the data analysis technique, and the results of the pre-test and post-test revealed that the data were not normally distributed, with Asymp.Sig.(2-tailed) less than 0.05. The Asymp.Sig.(2-tailed) value of the Wilcoxon test was less than 0.05. These findings suggest that there are changes in learning outcomes before and after using a PBL learning paradigm as a treatment. The pre-test and post-test mean scores were 53.71 and 84.57, respectively. An increasing in learning outcomes in electrochemical material is obtained by obtaining an effect size calculation value of 1.6, or the equivalent of 33% of the contribution of the PBL model.Based on the result of the pre-test & post-test there are difference in learning outcomes before and after using the PBL.